The evolution of private security jobs and security guards of the future - Perčin, Ante; Nađ, Ivan; Mihaljević, Branko (Crisis Management Days, 2024)
When looking at the private protection sector, we often deal with expected future projections, but without a realistic view of the current situation within the sector. Therefore, we believe that any prediction of the development of this dynamic sector, as well as of the professional and expert competencies of security guards as the fundamental bearers of protective activities, must be planned with a parallel review of the current market of private protection services. In this context, the goal of this work is a realistic overview of the current state of private protection in the Republic of Croatia and the key factors that contribute to it, the status of the direct executors of private protection, their current preferences, motivations and competences, as well as the projection of future training and education, in the context of the overall development and evolution within this sector. In accordance with what was stated in the projection for the future, we simultaneously perceive the fact that the Republic of Croatia is not isolated from the overall security trends in the environment, and therefore it is necessary to take into account all the realities of the changed security environment, new security threats, and on the basis of these new and evolving security the needs of service users, as well as parallel processes of continuous substitution of part of the jobs within the private protection sector, the process of pluralizing security jobs, and the necessity of adapting private protection jobs to the process of digital transformation of the business environment and the increasing participation of modern technology and technologically advanced systems when providing private protection services.